Evaluation of a portable clinical analyzer for the determination of blood gas partial pressures, electrolyte concentrations, and hematocrit in venous blood samples collected from cattle, horses, and sheep - Peiró, Juliana Regina [UNESP]; Borges, Alexandre Secorun [UNESP]; Goncalves, Roberto C. [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP] (Amer Veterinary Medical Assoc, 2010)
Objective To compare results reported for blood gas partial pressures, electrolyte concentrations, and Hct in venous blood samples collected from cattle, horses, and sheep and analyzed by use of a portable clinical analyzer (PCA) and reference analyzer (RA).Animals-Clinically normal animals (24 cattle, 22 horses, and 22 sheep).Procedures-pH; Pco(2); Po(2); total carbon dioxide concentration; oxygen saturation; base excess; concentrations of HCO(3)(-), Na(+), K(+), and ionized calcium; Hct; and hemoglobin concentration were determined with a PCA. Results were compared with those obtained for the same blood sample with an RA. Bias (mean difference) and variability (95% confidence interval) were determined for all data reported. Data were also subjected to analyses by Deming regression and Pearson correlation.Results-Analysis of Bland-Altman plots revealed good agreement between results obtained with the PCA and those obtained with the RA for pH and total carbon dioxide concentration in cattle, K(+) concentration in horses and sheep, and base excess in horses. Except for Na(+) concentration and Hct in horses and sheep, correlation was good or excellent for most variables reported.Conclusions and Clinical Relevance-Data from blood gas and electrolyte analyses obtained by use of the PCA can be used to evaluate the health status of cattle, horses, and sheep. Furthermore, the handheld PCA device may have a great advantage over the RA device as a result of the ability to analyze blood samples on farms that may be located far from urban centers. (Am J Vet Res 2010;71:515-521)